Hygiene auditing in mass catering: a 4-year study in a university canteen. (June 2018) - Osimani, A.; Milanović, V.; Aquilanti, L.; Polverigiani, S.; Garofalo, C.; Clementi, F.
Abstract: Objectives: The outcomes of hygiene audits carried out two times per year were used to determine the correct execution of the procedures foreseen by the Hazard Analysis and Critical Control Points (HACCP) plan over 4 years (2013–2016) in a university canteen producing about 1200 meals a day. Study design: Critical analysis of hygiene audits. Methods: Hygiene audits were carried out on the basis of a checklist divided into seven main items and subitems that covered all the production areas of the canteen. For each audit subitem, total percentage of inadequacy was calculated as the total number of negative answers (N) divided by the total number of answers (n = 8) collected in the period 2013–2016. Results: The results showed a discontinuous trend among years. In more detail, the highest percentage of inadequacy was seen for food maintaining temperatures, thus highlighting management issues mainly related to time taken for food preparation. A relatively high level of inadequacy was also recorded for staff clothing and hygiene. Conclusions: The critical analysis of data emerged from the audits was useful to obtain an overview of improvements and emerging criticalities. Highlights: Hygiene audits were used to assess the implementation of the HACCP system. A discontinuous trend was observed among years. Risk of cross-contamination between raw materials and ready-to-eat foods was observed. The results highlighted improvements and emerging criticalities over years.